ANALISIS FAKTOR HASIL BELAJAR DASAR TEKNOLOGI MENJAHIT SISWA TATA BUSANA DI SMK - Yuliana yuliana; Siti Mariah (UNIVERSITAS SARJANAWIYATA TAMANSISWA, 2017)
The purpose of this study is to know: Internal Factors and External Factors that affect the basic learning outcomes of sewing technology. The population of the study were the students of X class of fashion in SMK Negeri 1 Sewon Bantul Yogyakarta, which numbered 128 students from 4 classes. This study included is quantitative descriptive research. Technique of sampling usingproportional random sampling with amount of sample 74 student. The data collection technique used questionnaire and tested to 30 students outside the sample but still in one population. Data tested the validity, reliability and data analysis techniques product moment correlation. The results showed that the factors that influence the basic learning outcomes of technology sewing X class students in fashion majors most of the respondents in the category enough. Based on these data, the factors that influence the basic learning result of sewing technology are internal factor with 52,6%.Keywords: the factors that influence the learning outcomes.